Phosphorus fertilization in maize in northeastern of Pará state - Saldanha, Eduardo Cézar Medeiros; Rocha, Maria Eunice Lima da; Araújo, José Leandro Silva de; Alves, José Darlon Nascimento; Mariano, Daiane de Cinque; Okumura, Ricardo Shigueru (Revista de Ciências Agroveterinárias, 2018)
In Brazil, the maize crop has high production volume, and the State of Pará has the potential to become major center for grain production. However, it consists of tropical soils, which are acidic and low phosphorus availability. The aims of this study was to evaluate the growth and productivity of maize plants exposed to different rates of phosphorus in typical dystrophic Yellow Latosol in Capitão Poço city, Northeastern Pará State, in 2011. In the experimental area, soil correction was performed by liming, increasing the base saturation to 60%. The experimental design was a randomized block with four replicates, in which the treatments were: 0; 45; 90; 135 and 180 kg ha-1 of P2O5 applied at sowing, using triple superphosphate source (46% P2O5). The variables: plant height, stem diameter, number of leaves and number of ears showed a better adjustment of quadratic equation to application of P2O5 in sowing furrow with maximum technical efficiency obtained at rates of 142.1 kg ha-1; 114.62 kg ha-1; 130.59 kg ha-1 and 145 kg ha-1 of P2O5, respectively. The application of 179.87 kg ha-1 of v in corn crop (BR 5102 variety) in a typical dystrophic Yellow Latosol promoted yield of 6.58 t ha-1 of grains under the soil and climatic conditions of Capitão Poço region.